2016
DOI: 10.1002/ijop.12293
|View full text |Cite
|
Sign up to set email alerts
|

Individual and culture-level components of survey response styles: A multi-level analysis using cultural models of selfhood

Abstract: International audienc

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
56
0
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 55 publications
(58 citation statements)
references
References 23 publications
0
56
0
2
Order By: Relevance
“…In that context, although the factor structure and the strength of the associations between the items and the latent constructs of romantic avoidance and anxiety appear not to significantly differ between Greeks and Cypriots, intercepts (scores) of items included in the non-invariant parcels 1 (items: 25, 27, 31), 3 (items: 15, 17, 29), 4 (items: 5, 23, 33), 7 (items: 6,18, 30) and 11 (items: 14, 26, 36) need to be compared with caution. Cypriots (due to their exposure to the British common-wealth) may be more individualistic, emphasizing less the relational and more the individual aspect of romantic relationships (Smith et al, 2016;Terkourafi, 2007). Given that the ECR-R highlights more the individual romantic reference, different trends (i.e.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In that context, although the factor structure and the strength of the associations between the items and the latent constructs of romantic avoidance and anxiety appear not to significantly differ between Greeks and Cypriots, intercepts (scores) of items included in the non-invariant parcels 1 (items: 25, 27, 31), 3 (items: 15, 17, 29), 4 (items: 5, 23, 33), 7 (items: 6,18, 30) and 11 (items: 14, 26, 36) need to be compared with caution. Cypriots (due to their exposure to the British common-wealth) may be more individualistic, emphasizing less the relational and more the individual aspect of romantic relationships (Smith et al, 2016;Terkourafi, 2007). Given that the ECR-R highlights more the individual romantic reference, different trends (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, a smaller range and generally lower ECR-R scores in Greek (vs Cypriot; where higher individualism may induce more elevated scores and therefore, higher means/ item intercepts) adolescents could be assumed. This is reinforced by Greek-Cypriot differences in inter-correlations of romantic attachment scores (controlling for age and gender) and their perceptions of functional relationships (Georgas et al, 2001;Smith et al, 2016). In that context, the present study aims to examine the invariance of the ECR-R psychometric properties across Greek and Cypriot late adolescents.…”
Section: Greece and Cyprusmentioning
confidence: 95%
See 2 more Smart Citations
“…It is also possible that English and Italian participants report subjective responses differently. It has been shown that survey response style is strongly influenced by cultural models (Smith et al, 2016). Culture not only impacts self-assessment reports but also objectively impacts physiological responses to emotions (Lim, 2016 Blascovich, & Mccall, 2012).…”
Section: Discussionmentioning
confidence: 99%